2000
DOI: 10.3928/0098-9134-20000701-13
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Care: Perceptions of Certified Nurse's Aides

Abstract: Despite substantial attention devoted to the development of individualized care in nursing homes during recent years, empirical research assessing progress is limited. Further, few studies have explored the experiences of certified nurse's aides (CNAs) in this regard. This survey examines the perceptions and experiences of CNAs in providing individualized care. CNAs (n = 254) were asked to describe a number of current practices and obstacles to implementing individualized care in nursing homes. The majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…, Curry et al . ). Tellis‐Nayak () reported that a good ethical climate produced the energy for individualizing nursing care.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Curry et al . ). Tellis‐Nayak () reported that a good ethical climate produced the energy for individualizing nursing care.…”
Section: Introductionmentioning
confidence: 97%
“…The professional practice environment includes structural factors, for example communication systems and resources and social and behavioural factors, including teamwork (Curry et al . , Ives Erickson et al . ), social relations, leadership and management (Ives Erickson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Individualized care has been studied and conceptualized from both the patients' [3,11–14] and nurses' perspective [1,15–17]. Suhonen et al.…”
Section: Introductionmentioning
confidence: 99%
“…(Spore et al, 1991;Gallagher et al, 2006). Furthermore, many LTC staff members openly report having the need for training in mental health issues related to dementia (Curry et al, 2000;Pennington et al, 2003;Sung et al, 2005;Ramirez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%